Effect of Moxibustion in the treatment of spleen-stomach deficiency cold type epigastric pain and related nursing measures (香胡祛寒饼灸治疗脾胃虚寒型胃脘痛效果观察及护理) - WANG Qian (王倩); WANG Jiehong (王捷虹); SHA Zhihui (沙志惠) (Association of Integrative Nursing, 2024)
Objective Through the problem-oriented clinical syndrome differentiation thinking, the Xianghu dispelling-cold cake moxibustion was adopted in the treatment of spleen-stomach deficiency cold type epigastric pain, and related nursing measures were summarized. Methods The clinical data of 106 hospitalized patients with epigastric pain from September 2021 to August 2022, were selected and randomized into 2 groups. 53 cases in the control group received routine care, and 53 cases in the intervention group received Xianghu dispelling-cold cake moxibustion treatment on the basis of the control group. The symptom scores, time to pain relief, patient satisfaction and treatment compliance were observed and compared between two groups. Results the Traditional Chinese Medicine syndrome scores in both groups decreased after intervention, and Traditional Chinese Medicine syndrome scores in the intervention group decreased more significantly than those in the control group (P <0. 05). The pain relief time in the intervention group was significantly shorter than that of the control group, with a significant difference (P <0. 05). The patient satisfaction and compliance rates in the intervention group were higher than those of the control group, with a significant difference (P <0. 05). Conclusion The clinical application of Xianghu dispelling-cold cake moxibustion in the treatment of spleen-stomach deficiency cold type epigastric pain highlights the characteristics and advantages of Traditional Chinese Medicine, not only improves the quality of nursing care of Traditional Chinese Medicine, but also promotes the development of specialist nursing. (目的 通过以问题为导向的临床辨证思维, 探索香胡祛寒饼灸治疗脾胃虚寒型胃脘痛的效果, 总结护理经验。方法 选取2021年9月-2022年8月106例虚寒型胃脘痛住院患者的临床资料, 采用数字表随机方法随机分两组, 对照组 (n=53)给予常规护理, 干预组 (n=53)在对照组基础上给予香胡祛寒饼灸治疗。对比两组患者症状评分、疼痛缓解时间以及患者的满意度、依从性、烫伤发生率。结果 与干预前比较, 两组患者的中医症候积分均降低, 且干预组降低更加显著(P<0. 05); 干预组疼痛缓解时间较对照组缩短, 差异有统计学意义(P＜0. 05); 干预组患者满意度、依从性均高于对照组, 差异有统计学意义(P＜0. 05)。结论 通过香胡祛寒饼灸治疗虚寒型胃脘痛, 突出了中医特色与优势, 不但提高了中医专科疾病的护理质量, 而且促进了专科护理发展。)